Informing climate policy through institutional collaboration: reflections on the preparation of Colombia’s nationally determined contribution - Pinto, Alex de; Loboguerrero Rodriguez, Ana María; Londoño, Mario; Ovalle Sanabria, Katherine; Suarez Castaño, Rodrigo (Informa UK Limited, 2018)
The 2015 Paris Agreement was adopted at the twenty-first session of the Conference of the Parties (COP 21) to the United Nations Framework Convention on Climate Change (UNFCCC). In the run-up to COP 21, most UNFCCC Parties put forward intended nationally determined contributions (INDCs), containing mitigation pledges. These INDCs are now being confirmed as nationally determined contributions (NDCs), as governments formally ratify the Paris Agreement. NDCs are supposed to provide transparent, quantifiable, comparable, and verifiable mitigation objectives. However, there is neither methodological nor data consistency in the way Parties have prepared their NDCs. This article showcases recent collaboration among research, government, and private institutions that contributed to the Colombian NDC. While documenting the novel research, data, and rich web of collaboration that helped the Colombian government prepare the country’s NDC, this article links this specific case with the challenges of policy-oriented and interactive models of research. Our experience confirms previous research on the importance of stakeholder interaction, transparency and openness of processes, and willingness to break disciplinary and institutional barriers. In addition, the experience points to the importance of having appropriate available resources and a local institution acting as champion for the project.